Pedestrian Facility Design For Sports Centre Area In Small Town Of Indonesia (Case Study: Bima Sports Centre Area) - safii, Mochmad ibnu; NP, Subhan Hilmi; Hariani, Mira Lestira; Hardayani, Arni Muslimah (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
The largest public space in Cirebon City, Indonesia, is Bima Sports Center, with conditions that could be more conducive, resulting in the conversion of sidewalks that are not suitable for their function into areas for street vendors and illegal parking, which hurts the interests of pedestrians. This study aims to provide design recommendations (prototype) based on PU regulation no. 02/SE/M/2018 about pedestrian facility standards. The methods used in this research are the Pedestrian Level of Service (PLOS) approach in evaluating the performance of pedestrian facilities, the Customer Satisfaction Index (CSI) approach in assessing pedestrian satisfaction, and providing design recommendations based on the results of the CSI analysis. The research results show that the PLOS value in existing conditions varies from A - to F, and the main variables that determine pedestrian satisfaction are cleanliness, safety, and lighting facilities. Based on the analysis of the results, the design recommendation is to adjust the geometry according to standards and emphasize the Provision of cleaning facilities (bins), lighting, and safety fences along pedestrian paths.